Evaluation of sleep quality among nursing faculty: Application of the Pittsburgh Sleep Quality Index—A descriptive correlational study. Issue 1 (26th September 2021) - Cox, Sonya D.; Benoit, Julia S.; Brohard, Cheryl L.; McIntyre, Teresa M.
Abstract: Aim: The aim of this study was to describe the overall sleep quality, sleep patterns and severity of sleep difficulties among nursing faculty using the Pittsburgh Sleep Quality Index (PSQI). Design: Cross‐sectional descriptive and correlational study. Methods: A survey of faculty recruited from Texas Board of Nursing approved colleges/schools was used. A purposive, convenience sample of 105 faculty completed the PSQI, a reliable and valid instrument, in an online setting. Data was collected from January 2019 through April 2019. Results: Nursing faculty reported sleep difficulty across all components, with more problems in sleep latency, sleep disturbances and subjective sleep quality. Overall, 70.5% of participants were reportedly "poor" sleepers, a salient finding. Faculty experienced poor sleep quality across all academic ranks and age groups. Sleep latency and subjective sleep quality were components that presented higher in severity for the youngest faculty.